Pengembangan Metode Permainan Teka Teki Untuk Meningkatkan Minat Siswa Dalam Belajar Bahasa Mandarin Dengan Menggunakan Pendekatan Design Thinking - Sofyanti, Sofyanti; Aripradono, Heru Wijayanto (Universitas Hamzanwadi, 2023)
The introduction of Mandarin as a foreign language is increasingly important in the era of globalization and increasingly close international relations between countries. In many countries, including Indonesia, the ability to speak Mandarin is considered a competitive advantage in various fields. Despite its importance, interest in learning Mandarin is still low. The purpose of this study is to identify and analyze the effect of the puzzle game method in increasing students' interest in learning Chinese. This study used qualitative research methods. Data collection techniques were carried out by observation and literature study. The data that has been collected is then analyzed thematically. The results showed that efforts to increase students' interest in learning Chinese, namely by playing charades implemented through power point media at Zoom meetings, proved to be able to increase students' interest in learning Chinese because it was considered interesting and fun by students. In addition, in this game there are also prizes for students who have the highest points. Points are obtained by answering questions correctly, this makes students eager to collect points and indirectly increases students' interest in learning.